Private interests and public money : the state provision of medicines in New Zealand 1938-1986 : a thesis presented in fulfilment of the requirements of the degree of Doctor of Philosophy at Massey University - Baker, Astrid Theresa; Baker, Astrid Theresa (Massey University, 1996)
Provision for free medicines was one aspect of the universal health service outlined in Part III of Labour's Social Security Act 1938. The official arrangements made during the next three years to supply medicines under the Pharmaceutical Benefits Scheme were intended to benefit the ill, but also protected the interests of doctors and pharmacists. The Government's introduction of these benefits coincided with dramatic advances in organic chemistry and the subsequent development of synthetic drugs in Europe and the United States. These events transformed the pharmaceutical industry from a commodity business to a sophisticated international industry producing mainly synthetic, mass-produced medicines, well protected by patents. While no government in the early 1940s could have guessed at the cost of providing such products, no government committed to a public health service could deny these products once they were commercially available. Pharmaceutical benefits quickly became a crucial aspect of patients' rights to free medical care in general but, at the same time, represented income and profit to pharmacists, drug manufacturers and wholesalers, and an important aspect of doctors' professional and economic status. This tension between state commitments and private interests, still unresolved, is the central theme of this history. Through its control of access to the New Zealand market, the Department of Health was in theory in a strong position to bargain with local producers over drug prices. But in practice it was powerless to confront individual companies which held the patents on behalf of their overseas parent companies. Indeed the policies of the Department of Industries and Commerce were crucial in promoting the prosperity and profits of this small local pharmaceutical industry so as to guarantee access to paid employment and conserve precious foreign exchange. New Zealand was not alone in grappling with such problems and conflicts of interest. Governments in the United Kingdom, the United States, Canada and Australia all had great difficulty controlling doctors' prescribing, and also had ambivalent aims when bargaining with local pharmaceutical manufacturers and importers. This thesis contributes to many studies on collaboration and compromise in government policy. It vividly demonstrates Heclo and Wildavsky's claim that governments operate as a federation of departments each linked to client groups. More importantly, this New Zealand history of the state provision of medicines extends and modifies British, Canadian, United States and Australian literature on the politics of national health services. Because discussion of state-funded and state-organised prescription medicines schemes in these studies is dominated by the politics of the medical profession, pharmaceutical companies and pharmacists are often only a shadowy presence. This thesis, for the first time, brings together the history of the medicines themselves, and the way in which they came to mean different things to each different provider - to doctors, drug companies, pharmacists and the state itself. An understanding of the history of this one aspect of government health services also enriches our understanding of the wider history of the New Zealand welfare state.
Keywords: Government policy; Pharmaceutical industry; Prescription medicines; Subsidised medicine